The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1093/gbe/evad001
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-Level Genome Assembly of the Cape Cliff Lizard (Hemicordylus capensis)

Abstract: Squamates represent a highly diverse and species-rich vertebrate group that is remarkably understudied from a genomic perspective. A scarcity of genomic data is particularly evident for scincomorph lizards, which encompass over 10% of all living squamates, and for which high-quality genomic resources are currently lacking. To address this knowledge gap, we present the first chromosome-level reference genome for this group, generated from a male Cape cliff lizard (Hemicordylus capensis), using highly accurate P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The observed molecular weight was almost identical to that calculated from the identified amino acid sequence. A database exploration revealed that C25 had a high similarity to partial sequences of beta-enolase enzymes [ 27 ]. The secondary structure was suggested by using the GOR method, which indicated that C25 potentially forms extended strands and random coils ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observed molecular weight was almost identical to that calculated from the identified amino acid sequence. A database exploration revealed that C25 had a high similarity to partial sequences of beta-enolase enzymes [ 27 ]. The secondary structure was suggested by using the GOR method, which indicated that C25 potentially forms extended strands and random coils ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structure was suggested by using the GOR method, which indicated that C25 potentially forms extended strands and random coils (Figure 3). exploration revealed that C25 had a high similarity to partial sequences of beta-eno enzymes [27]. The secondary structure was suggested by using the GOR method, wh indicated that C25 potentially forms extended strands and random coils (Figure 3).…”
Section: Generation Purification and Structural Analysis Of The Chick...mentioning
confidence: 99%
See 1 more Smart Citation